Bench detail of AT1 & AT2 (RFA-522_Rev.A) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.